(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Medical education reforms in South Asia have introduced integrated teaching, competency‑based modules, and diverse assessments such as SBA, PBQ, SEQ, and MCQ formats. Evaluating student perceptions of these changes is crucial to assess their feasibility and educational effectiveness. Objective: To analyze student perceptions of the MBBS Phase‑I curriculum’2021 and its assessment modalities, and to identify strengths and challenges in implementation. Methods: A structured 33-item questionnaire (Google Form) was distributed among Phase‑I MBBS students (N=380). Responses were recorded on a four-point “Likert scale” (Very much, Yes, Not so much, No) and analyzed quantitatively using descriptive statistics. Items were grouped thematically into categories: Integrated classes, generic and humanitarian topics including Ethics, SBA, PBQ, SEQ, MCQ, and understanding type of questions. Data were processed using Python and summarized with tables and visual charts. Results: Generic items achieved the highest mean ratings (≈2.98–2.99/4). PBQ and integrated class items followed with moderate means (≈2.83–2.73). SBA, SEQ, and MCQ items scored lower (≈2.4–2.6), indicating comparative difficulty or reduced enthusiasm. Students perceived PBQs as engaging, while SBAs were viewed as challenging for Phase‑I. Conclusion: Phase-I students are receptive to the new curriculum’2021, particularly generic, integration and PBQs. Additional formative sessions and feedback for understanding type of questions, SBA/MCQ-based assessments may enhance acceptance and learning outcomes. J Com Med Col Teachers’ Asso Jan 2026; 30(1): 50-52